PENGARUH DAYA TARIK, FASILITAS DAN AKSESIBILITAS TERHADAP KEPUASAN WISATAWAN DI OBJEK WISATA PONDOK HALIMUN - Oktavan, Doa Galank; Siswandi, Zerry; Ruswandi, Wawan (JCI Publisher, 2026)
This study aims to examine the influence of tourist attractions, facilities, and accessibility on tourist satisfaction at the Pondok Halimun Tourist Destination, Sukabumi Regency. The research employed a quantitative approach using a causal associative design. The population consisted of tourists who visited Pondok Halimun between April and July 2025. A total of 95 respondents were selected using accidental sampling techniques. Data were collected through questionnaires measured on a five-point Likert scale and analyzed using multiple linear regression with SPSS software. The results indicate that tourist attractions, facilities, and accessibility individually have a positive and significant effect on tourist satisfaction. Furthermore, the simultaneous test confirms that these three variables collectively have a strong influence on tourist satisfaction. The coefficient of determination reveals that a substantial proportion of tourist satisfaction can be explained by the combined effects of tourist attractions, facilities, and accessibility. These findings suggest that integrated destination management focusing on attraction quality, adequate facilities, and ease of access is essential to enhance tourist satisfaction and support sustainable tourism development.